Building on MaineCare’s Success - Pohlmann, Lisa; Hastedt, Christine (Maine Policy Review, 2007)
This commentary provides a particular viewpoint on MaineCare (Maine’s Medicaid program). Lisa Pohlmann and Christine Hastedt critique reform efforts in several states and emphasize the key role of MaineCare in the state’s overall health care system.
Keywords: Maine; MaineCare; Medicaid